IMPLEMENTASI MANAJEMEN SUMBER DAYA MANUSIA BERLANDASAKAN HUKUM PENDIDIKAN DI INDONESIA - Galuh Ratnagung, Catur; Suryani, Lilis; Ratnasih, Pancagaluh (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
The objectives of the Indonesian state are explicitly defined in the preamble to the 1945 Constitution, namely to defend the entire Indonesian nation and all Indonesian bloodshed, advance the welfare of the people, educate the nation's life, and contribute to implementing world order. Therefore, the State builds a government system that strives to achieve the overall and sustainable objectives of the state based on Pancasila and the 1945 Constitution. The subject of education quality remains a critical concern addressed by the Indonesian state. The gap in education quality, both across regions, between private and public educational institutions, and other issues continue to be raised and become a passive discussion that appears in the public arena. In order to improve the quality of education, in 2005 the government released Indonesian Regulation number 19 of 2005 concerning National Education Standards, this regulation is the government's effort to improve the quality of education in Indonesia. Government regulations state: 1. The learning process in an educational unit is held interactively, inspiringly, fun, challenging, motivating students to achieve actively and providing sufficient space for initiative, creativity and independence in accordance with the talents, interests and physical and psychological development of students, 2. In the learning process, educators are required to be able to provide examples (as role models, good examples for students), 3. Each educational unit plans the learning process, implements the learning process, assesses learning outcomes, and supervises the learning process for the implementation of an active and dynamic learning process. (Moh. Saifulloh, Zainul Muhibbin, 2012). This study aims to explore the implementation of human resource management (HRM) in the context of educational law in Indonesia. Considering the important role of human resources in improving the quality of education, this study will examine how educational policies and regulations can influence HR management practices in educational institutions. Through data analysis and case studies, it is hoped that this study can provide useful recommendations for the development of more effective educational policies. This research is by collecting data with Internet sources and other literary sources and then concluding based on existing data. The product of this research is a national journal with issn.